Executive Summary: Global Health and Emergency Care—What Do We Need to Know to Address the Burden of Illness and Injury?. (December 2013) - Hargarten, Stephen; Martin, Ian B.K.; Hauswald, Mark; Hirshon, Jon Mark; Cone, David C.
Abstract Emergency physicians are uniquely poised to address challenges in health services, health care systems development and management, and emerging global disease burdens (both communicable and noncommunicable). This special issue of Academic Emergency Medicine reports the results of the 2013 consensus conference, which included eight focus areas that are intended to advance emergency care research. Advancing our understanding of cardiac and injury resuscitation, ethics of research, health systems development, and the education of our future leaders in global health will ultimately affect the populations of all nations across the globe.